Poverty Analysis and Inequality Distribution in Yogyakarta Special Region - Dewi, Yulian Anshita; Rachmawatie, Dessy (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to analyze Poverty Inequality and Inequality of Regency/ City Revenue Distribution in Yogyakarta Province D.I. Secondary data here uses data between places or spaces (cross-sections) taken from all districts/cities in Yogyakarta, while data for time series data is taken in 2009-2015 where this data is data collected in a certain time period. Data which is a combination of cross-section and time-series data used in this study is called panel data. The paper using literature review approach and metadata analysis. In this study, the results show that the human development index variable, GRDP, local original income, general allocation funds affect the Inequality of the District Revenue / City Distribution in Yogyakarta.